ONLINE RESERVATION SYSTEM AND ONLINE CUSTOMER REVIEW: ITS IMPACT ON BRAND IMAGE, TRUST AND HOTEL BOOKING DECISION - Nurul Faliha; Astuti Endang Siti; Rahardjo Kusdi; Kusumawati Andriani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Digital marketing is currently a new force in marketing strategy. The marketing mix in hotel digital marketing applies an online reservation system as a distribution channel and online customer review as a promotional tool. The use of the online reservation system will distribute hotel rooms throughout the world. The market potential will not be limited by time or distance. This technology is a mainstay for hotels to distribute rooms to customers. The use of online customer review as a promotional tool is carried out by asking customer's participation to express their review of the product to potential customers. This method is widely used as customer's words is more trusted than vendors’. The objective of the present study is to investigate the role of digital marketing strategies, especially the impact of the online reservation system and online customer review on brand image, trust, and hotel booking decision. This study utilizes a literature review from previous studies that are relevant to this study. Articles were taken digitally using google search engine with the keywords